1997
DOI: 10.1021/jf9703157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Synthetic Sucrose Esters on Weed Seed Germination and Crop Growth:  Structure−Activity and Dose−Response Relationships

Abstract: Twelve synthetic sucrose ester (SE) products with C7−C10 chain lengths and various degrees of esterification (DE) were tested for their influence on seed germination of prosomillet and velvetleaf and on growth of broccoli and bell pepper plants. At 100 ppm most SE caused virtually total inhibition of germination; at lower concentrations dose−response and structure−activity relationships were apparent. Sucrose esters with seven and eight carbon acyl groups were most effective, and activities decreased for nonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Although these products were appropriate for controlling the adult silverleaf whiteflies, the growers should also consider some other factors prior to the utilization. The effect of sucroesters on plant development, on the seed germination (Peterson et al 1997), and on the natural enemies should also be investigated. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these products were appropriate for controlling the adult silverleaf whiteflies, the growers should also consider some other factors prior to the utilization. The effect of sucroesters on plant development, on the seed germination (Peterson et al 1997), and on the natural enemies should also be investigated. …”
Section: Resultsmentioning
confidence: 99%
“…An anionic surfactant, sodium dodecylsulfate (SDS) was also applied for the comparisons. Whiteflies bioassays were carried out with the adult insects collected from the cabbage plants using the yellow sticky strips with 4 x 4 cm of exposed surface (Chortyk et al, 1997). Nine strips (replicates) were used per treatment onto which ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cucumber accessions have shown allelopathy to proso millet in the field [see section 13(c)]. Peterson et al (1997) tested 12 different synthetic sucrose esters for their ability to inhibit the germination of seeds of Panicum miliaceum and velvetleaf. Tests in Petri dishes revealed that ten of the synthetic sucrose esters could cause more than 90% inhibition of germination in P. miliaceum when applied at a concentration of 100 ppm and one of these esters could cause 80% inhibition at a concentration of 10 ppm.…”
Section: (Iii) Weedsmentioning
confidence: 99%